E-Learning Experiences of Bachelor of Science in Public Health Students of PUMHSW (S.B.A) During the Period of Covid-19 in 2020 - Shahbaz, Kiran; Naz, Fahmida; Khanum, Zubeda; Shaheen, Farkhanda; Saima, Saima; Bibi, Fatima (Mandalika Institute, 2024)
An e-learning is an important part of new-age education, where students obtain materials electronically using the different software system. These systems allow students to learn at any time and from any place through the Internet. Difficulties, like adapting to the online environment, frequently cloud the students' learning process. The goal of this research is to determine how e-learning affects university students studying to see if they are still expecting that to be a coming classroom. Data was collected from 188 students enrolled in PUMHSW, Shaheed Benazirabad using a quantitative research approach. Training on data till up to Oct 2023. The findings reveal significant challenges in e-learning arrangements, including poor internet connectivity, lack of electronic devices, frequent power outages, and distractions caused by an unconducive learning environment. These issues collectively paint a grim picture of the e-learning experience for students.To improve e-learning effectiveness, universities should focus on strengthening digital infrastructure, ensuring access to necessary devices, and promoting blended learning models that combine online and offline teaching. Providing technical support and training for students and faculty can further enhance the online learning experience.